The Interplay between NLRs and Autophagy in Immunity and Inflammation - Carneiro, Leticia A.; Travassos, Leonardo H. (Frontiers in Immunology, 2013)
Since they were first described as cytosolic sensors of microbial molecules a decade ago, the Nod-like receptors (NLRs) have been shown to have many different and important roles in various aspects of immune and inflammatory responses, ranging from antimicrobial mechanisms to control of adaptive responses. In this review, we focus on the interplay between NLRs and autophagy, an evolutionarily conserved mechanism that is crucial for homeostasis and has recently been shown to be involved in the protective response against infections. Furthermore, the association between mutations of NLRs as well as proteins that form the autophagic machinery and inflammatory diseases such as Crohn’s disease highlight the importance of these proteins and their interactions in the regulation of inflammation.